STATEMENT OF FEMINISM MOVEMENT FIGURE IN NOVEL : AISYAH “ WANITA YANG HADIR DALAM MIMPI RASULULLAH “ - Siregar, Diana Rumondang; Siringo-ringo, Kristina; Situmorang, Nursitta; Yunanda, Fachri (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
A B S T R A C TThis study aims to describe the characterization of feminism movement figures in Sibel Eraslan's novel “ Aisyah ( Wanita Yang Hadir Dalam Mimpi Rasulullah )”, which reflects the reality of women's lives and the struggle for equality between men and women. The author is interested in researching this novel, because this novel is able to present wise or intelligent female characters in carrying out feminist movements to break down those who narrow the space for women's movements by using the feminist literary criticism approach. The research data is qualitative data in the form of facts, information, statements or descriptions obtained by researchers from research sources, namely the novel Aisyah ( Wanita Yang Hadir Dalam Mimpi Rasulullah ) by Sibel Eraslan. The data collection technique uses descriptive qualitative methods that focus on content analysis, which is an in-depth analysis of the content of written information.